Assessment Report on Mbonge & Bakundu Tribal Areas – Kumba Division, Cameroons Province 2 (Colonial Letters and the Contact of Knowledges, 1922)
This file contains colonial assessment report on Mbonge & Bakundu in Kumba Division including a map
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies